PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA KONSUMEN PT. LONTAR MEDIA DIGITAL PRINTING SEMARANG) - Hilman Ardianta Putra; Ngatno Ngatno (Universitas Diponegoro, 2017)
PT. Lontar Media Digital Printing Semarang is one of the big service printing company in Semarang precisely in Sampangan area. The rapid development Lontar Media printing it turns out there are problems in sales fluctuant past several years.The purpose of this research is to know the service quality effect on customer loyalty through customer satisfaction as an intervening variable. This research type is explanatory research, with the techniques of data collection through the questionnaire. Sampling techniques using a purposive sampling technique. The sample in this research are 100 respondents which is a PT. Lontar Media Digital Printing Semarang customer. This research using techniques of quantitative analysis. Quantitative analysis using the test validity, reliability test, coefficient of correlation, linear regression analysis, the determination coefficient, and significance test with SPSS 16.0. The influence of mediation evidenced by sobel test and mediation test. The results of the research indicate that there is a positive effect and significant of the service quality variable to customer satisfaction of 0,190. There is a positive effect and significant of the service quality variable to loyalty customer of 0,227 There is a positive effect and significant of the customer satisfaction variable to loyalty customer of 1,028. Based on the results of the sobel test, known that there is a positive effect and significant of the service quality variable on customer loyalty variable through customer satisfaction variable as an intervening variable of 6,353. Based on the results of the mediation test, then the variable customer satisfaction can be said to be a partial mediation variable because all of the correlation is positive and all significant < 0.05. Disadvantages of service are evaluated as giving priority to the problems faced by consumers, individualized services most highlighted by corporate customers. Therefore it is used as an evaluation material for better service. There are still shortcomings and also advantages in this category of satisfaction, for that company needs to improve in terms of which is the weakness of an improved product marketing and service. In the loyalty variable it is seen that consumers are still hesitant to always go to this company. In order for loyal customers the company must set marketing strategy and evaluation about better service so that consumers are satisfied and make loyal again. Researchers are aware that in this study there are still shortcomings such as lack of other variables that usually affect the results of consumer loyalty. For the next research, the authors suggest adding other variables such as price, product quality, brand quality, service quality, and other variables. Subsequent research should also better control the selection of samples, add or trim indicator/item statement in accordance with the needs, for the next research to get more optimal results again.